1995
DOI: 10.3109/10611869509015955
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight-dependent Lymphatic Transfer of Fluorescein Isothiocyanate-labeled Dextrans after Intrapulmonary Administration and Effects of Various Absorption Enhancers on the Lymphatic Transfer of Drugs in Rats

Abstract: We have developed a new method to evaluate the transfer of macromolecular drugs to intrapulmonary lymph nodes in rats after intrapulmonary administration. By using this method, we observed that the transfer of fluorescein isothiocyanate dextrans (FDs) to the intrapulmonary lymph nodes was markedly higher than that to iliac lymph node, a non-intrapulmonary lymph node. The transfer of FDs to the intrapulmonary lymph nodes increased with increasing their molecular weights and the threshold for a high lymph node-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Under basal conditions or after intentional induction, lymphoid tissue may also play a role in the uptake of nanomaterials from the lungs 150 . Several studies have demonstrated uptake of inhaled nanoparticles, including liposomes 154 , 20-70 kDa dextrans 155 , non-cationic organic and inorganic nanoparticles of ≤ 34 nm 156 and antigen carrying lipid nanocapsules 157 into lung lymph nodes. Several other studies have inferred lung lymphatic involvement in the systemic availability of inhaled solid lipid nanoparticles 158 , liposomes 159 and 50-900 nm polystyrene nanoparticles 160 .…”
Section: Mucosal and Other Routes Of Deliverymentioning
confidence: 99%
“…Under basal conditions or after intentional induction, lymphoid tissue may also play a role in the uptake of nanomaterials from the lungs 150 . Several studies have demonstrated uptake of inhaled nanoparticles, including liposomes 154 , 20-70 kDa dextrans 155 , non-cationic organic and inorganic nanoparticles of ≤ 34 nm 156 and antigen carrying lipid nanocapsules 157 into lung lymph nodes. Several other studies have inferred lung lymphatic involvement in the systemic availability of inhaled solid lipid nanoparticles 158 , liposomes 159 and 50-900 nm polystyrene nanoparticles 160 .…”
Section: Mucosal and Other Routes Of Deliverymentioning
confidence: 99%
“…Studies have previously shown local uptake of pulmonary administered nanoparticles [220], including liposomes [221], dextrans [222] and solid lipid nanoparticles [223] into lung lymph nodes. For example, Choi et al showed that the physicochemical properties of nanoparticles (inorganic/organic hybrid particles and quantum dots) dictate trafficking across the alveolar barrier, as well as distribution and clearance [224].…”
Section: Inhaled Immunotherapies -Accessing Local Tumours and Drainin...mentioning
confidence: 99%
“…500 nm (Leak and Ferrans Lee, 1991;McIntire et al, 1998). Moreover, phagocytic activity of bronchoalveolar macrophages seem to be responsible for engulfing foreign particles, thus acting as vectors to the lymphatics (Langenback et al, 1990;Hanatani et al, 1995;Corry et al, 1984). Correlation between submicrometric mean diameter, deep lung deposition and lymphatic uptake is expected to be the basis for pulmonary drug delivery using colloidal carriers.…”
Section: Introductionmentioning
confidence: 99%
“…However, after intravenous administration, uptake of colloidal particles by the mononuclear phagocytic system (MPS) reduces circulation time and decreases targeting, thus limiting their application. Alternative administration routes have been studied indicating that nanoparticles can migrate to regional draining lymph nodes after subcutaneous or intraperitoneal injection (Wolf et al, 1994;Hanatani et al, 1995). An interesting approach for targeting drug carriers to the lymphatics involved the latter, resulting in significant lymphatic uptake, although particles (500 nm) remained in the abdominal cavity and targeting was restricted to thoracic lymph fluid, mediastinal and renal lymph nodes (Hanatani et al, 1995).…”
Section: Introductionmentioning
confidence: 99%